2012
DOI: 10.1186/1748-717x-7-117
|View full text |Cite
|
Sign up to set email alerts
|

Can exhaled NO fraction predict radiotherapy-induced lung toxicity in lung cancer patients?

Abstract: BackgroundA large increase in nitric oxide fraction (FeNO) after radiotherapy (RT) for lung cancer may predict RT-induced lung toxicity.MethodsIn this study, we assessed the relationships between FeNO variations and respiratory symptoms, CT scan changes or dose volume histogram (DVH) parameters after RT. We measured FeNO before RT, 4, 5, 6, 10 weeks, 4 and 7.5 months after RT in 65 lung cancer patients.ResultsEleven lung cancer patients (17%) complained of significant respiratory symptoms and 21 (31%) had radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…We previously reported that subsequent to RT or combined chemo-RT in 29 patients, the eNO level had decreased by 35% immediately subsequent to the completion of 40 Gy RT (6). The decrease in the eNO level observed following the treatment of chest malignancies is caused by cell death in the tumor and the surrounding tissues; this may also be accompanied by a reduction in tumor-associated inflammation, including cytokine production (17). The present study confirmed our previous data, demonstrating that RT reduced the levels of eNO.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that subsequent to RT or combined chemo-RT in 29 patients, the eNO level had decreased by 35% immediately subsequent to the completion of 40 Gy RT (6). The decrease in the eNO level observed following the treatment of chest malignancies is caused by cell death in the tumor and the surrounding tissues; this may also be accompanied by a reduction in tumor-associated inflammation, including cytokine production (17). The present study confirmed our previous data, demonstrating that RT reduced the levels of eNO.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patients were divided: the symptomatic RP group (SRP, with the CTCAE v4.0 score ≥ grade 2) and the asymptomatic RP group (ASRP, with CTCAE v4.0 score as grade 0 or 1) [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Some recent studies revealed reduction of mutated KRAS oncogene in EBC [40] and some VOCs in exhaled breath [41] after surgical resection of pulmonary tumor, particularly nonsmall cell type. Unfortunately, a recent study demonstrated that serial FE NO measurements during radiotherapy in patients with pulmonary cancer had a low ability to detect symptomatic radiation pneumonitis [42]. …”
Section: Exhaled Markers In Pulmonary Cancermentioning
confidence: 99%